2022
DOI: 10.1007/s11739-022-02975-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laboratory-verified smoking on SARS-CoV-2 infection: results from the Troina sero-epidemiological survey

Abstract: Previous research yielded conflicting results on the association between cigarette smoking and risk of SARS-CoV-2 infection. Since the prevalence of smoking is high globally, the study of its impact on COVID-19 pandemic may have considerable implications for public health. This study is the first to investigate the association between the SARS-CoV-2 antibody sero-positivity and biochemically verified smoking status, to refine current estimates on this association. SARS-CoV-2-specific IgG and serum cotinine lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…The observed association of smoking with decreased seropositivity was strong, stable across timepoints and subgroups, persistent when adjusted for potential confounding factors, and underscored by a dose–response association. The observed association with odds ratios around 0.5 were similarly observed in previously published seroprevalence studies of different designs [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Altogether, this supports a genuine relationship between smoking and lower seropositivity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed association of smoking with decreased seropositivity was strong, stable across timepoints and subgroups, persistent when adjusted for potential confounding factors, and underscored by a dose–response association. The observed association with odds ratios around 0.5 were similarly observed in previously published seroprevalence studies of different designs [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Altogether, this supports a genuine relationship between smoking and lower seropositivity.…”
Section: Discussionsupporting
confidence: 87%
“…SARS-CoV-2 antibodies measured in serum of population-based studies’ participants provide insights into the proportion of individuals who have experienced infection. SARS-CoV-2 infection-mediated seroprevalence has been reported to be increased for medical personnel and decreased for smokers in numerous studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], including two studies from Germany [ 11 , 12 ] as well as our baseline (BL) assessment of the Tirschenreuth Study (TiKoCo) [ 13 ]. With the exception of [ 12 ], these results were based on cross-sectional data collected shortly after the first pandemic wave (summer 2020) or in fall 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The risks of repeated muscle pain, fever and nausea were significantly lower in tobacco smokers. The study of smoking in the COVID-19 era has caught research attention since very first epidemic weeks [ 37 , 38 , 39 , 40 ]. The negative correlation between smoking and humoral response to vaccines has been widely described [ 41 , 42 ], and the lower occurrence of AEFI in smokers suggests a potential ancillary effect of tobacco use on the impairment of adequate innate and adaptive immune responses that underpin AEFI occurrence and, as is likely, general COVID-19 vaccine responses, which also reflect the change in smokers’ risk of breakthrough infection compared with the same risk in the pre-vaccination era [ 8 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, smokers may have avoided infection-prone settings due to awareness of their increased risk of severe disease. However, several studies have suggested that smoking is associated with overall reduced levels of IgA, IgG and IgM titers, and of IgG following SARS-CoV-2 infection or COVID-19 vaccination, 55 , 56 , 57 , 58 , 59 hence a lower seroprevalence among smokers could be an artefact.…”
Section: Discussionmentioning
confidence: 99%